Differences in Electromyograms during Horseback Riding between Professional and Amateur Korean Horse Riders - Young-Shik HWANG; Na-Ri HWANG; Dai-Hyuk CHOI; Wi-Young SO (Tehran University of Medical Sciences, 2021)
No Abstract